2014
DOI: 10.1115/1.4027937
|View full text |Cite
|
Sign up to set email alerts
|

The Regional Sensitivity of Chondrocyte Gene Expression to Coactive Mechanical Load and Exogenous TNF-α Stimuli

Abstract: Both mechanical load and elevated levels of proinflammatory cytokines have been associated with the risk for developing osteoarthritis (OA), yet the potential interaction of these mechanical and biological factors is not well understood. The purpose of this study was to evaluate the response of chondrocytes to the effects of dynamic unconfined compression, TNF-a, and the simultaneous effects of dynamic unconfined compression and TNF-a. The response to these three treatments was markedly different and, taken to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 50 publications
0
11
1
Order By: Relevance
“…The interaction between the various components of the model is critical to understanding OA at a systems level. For example, in the framework of this model previous studies 7, 30 have shown that healthy cartilage responds positively to load, where specifically the ratio of medial-to-lateral cartilage thickness was associated with the adduction moment during walking for healthy young subjects, whereas cartilage thickness in patients with medial knee OA responds negatively to a higher adduction moment 3 . Thus at a systems level there was an association between a mechanical signal and a structural measure of cartilage health.…”
Section: A Systems Model For Oamentioning
confidence: 96%
See 1 more Smart Citation
“…The interaction between the various components of the model is critical to understanding OA at a systems level. For example, in the framework of this model previous studies 7, 30 have shown that healthy cartilage responds positively to load, where specifically the ratio of medial-to-lateral cartilage thickness was associated with the adduction moment during walking for healthy young subjects, whereas cartilage thickness in patients with medial knee OA responds negatively to a higher adduction moment 3 . Thus at a systems level there was an association between a mechanical signal and a structural measure of cartilage health.…”
Section: A Systems Model For Oamentioning
confidence: 96%
“…It is possible that the limited success of the anti-cytokine intervention might stem from the potential interaction of the pro-inflammatory cytokines with mechanical factors. In laboratory studies 6, 7, 34 it was shown that the anabolic/catabolic response of the chondrocyte to the levels of pro-inflammatory cytokines is dependent on the nature of the mechanical load. In addition, the response can be sensitive to local regional differences as illustrated in Figure 3.…”
Section: A Systems View Of Oa Risk Factorsmentioning
confidence: 99%
“…Cytokines originate primarily from cells in the synovial lining; subsequent increase in cytokine signaling can lead to recruitment of additional immune cells to the inflamed area, and the newly recruited cells produce even more cytokines. These small proteins diffuse into cartilage [8] and bind to cell receptors on chondrocyte (cartilage cell) surface, thus regulating the balance of anabolic and catabolic gene expression in cartilage [31]. Some cytokines in cartilage are pro-anabolic (anti-inflammatory), such as transforming growth factor beta (TGF-β), interleukin (IL)-1 receptor antagonist, IL-4, IL-10, and erythropoietin [22,28,32].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, biological factors such as elevated systemic inflammation have been associated with the development and progression of knee OA 12 . Increased pro-inflammatory cytokines in the joint synovial fluid can have a profound catabolic effect on the cellular response of cartilage due to loading 6 , suggesting an interaction between mechanical loading and inflammation leading to cartilage degradation. These local increases in inflammation at the knee can be reflected in increased systemic, serum-derived proinflammatory cytokine levels, and vice versa 12e14 .…”
Section: Introductionmentioning
confidence: 99%